Chloro(2,3,7,8,12,13,17,18-octaethylporphyrinato)iron(III) - SENGE, MATHIAS (My University, 2005)
The molecular structure of the title compound, [Fe(C36H44N4)Cl], was determined by single-crystal X-ray diffraction at 130 K. The compound is characterized by an average Fe?N bond length of 2.071 (2) A E and an Fe?Cl bond length of 2.231 (1) A
PUBLISHED
Keywords: molecular structure; molecular structure